The Adjectives as a Word Class in Arabic: The Linguistic Analysis: Linguistic Analysis - Naknawa, Dulyawit (Journal of Letters, 2020)
Traditional Arabic grammar divides Arabic words into 3 categories: nouns, verbs and prepositions. Adjectives are not a traditional word class, but realized as syntactic positions in sentences, an approach which is followed in practice. However, the researcher proposes that adjectives should be considered a distinct word class separate from nouns. This is based on various evidence, such as typology, morphology and syntax. In certain contexts, adjectives can appear instead of nouns or eventually decategorize to noun but this does not mean that Arabic should have no adjective category.